2007
DOI: 10.4269/ajtmh.2007.76.703
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Hiv and Syphilis in a Remote Native Community of the Peruvian Amazon

Abstract: Little data are available on how HIV and other sexually transmitted infections (STIs) affect indigenous people in Latin America, including Peru. We conducted a sero-epidemiologic survey of HIV infection and syphilis in a native community, the Chayahuita, an indigenous population in the Amazon region of Peru. The seroprevalences of HIV and syphilis in adults were 7.5% (6 of 80) and 6.3% (5 of 80), respectively. None of the participants had ever used a condom. Male to male sexual behavior was common. At the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
49
0
14

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 7 publications
0
49
0
14
Order By: Relevance
“…Syphilis infection has reached alarming rates (13.8%-19.5%) in China 12. In the Peruvian Amazon, it was 6.3% 13. Different studies have reported the prevalence of active syphilis as follows, 9% in Northwestern Tanzania, 1.8% in China, 4% in South Africa and 0.2% in South Korea 14–17.…”
Section: Discussionmentioning
confidence: 99%
“…Syphilis infection has reached alarming rates (13.8%-19.5%) in China 12. In the Peruvian Amazon, it was 6.3% 13. Different studies have reported the prevalence of active syphilis as follows, 9% in Northwestern Tanzania, 1.8% in China, 4% in South Africa and 0.2% in South Korea 14–17.…”
Section: Discussionmentioning
confidence: 99%
“…The research findings by Zavaleta et al (2007) tend to stigmatize the studied community with respect to homosexual behaviors, early initiation of sexual activity and polygamy, and the high frequency of syphilis and HIV in Chayahuitaes. However, these results may not be representative of the whole community, as the number of study participants was only 162, which is 0.78 % of the total Chayahuita population of 20,540 inhabitants (Instituto Nacional de Estadística e Informática and Fondo de Población de las Naciones Unidas 2010).…”
mentioning
confidence: 85%
“…To the Editor: The letter by Zavaleta et al (2016) challenges our opinion (Minaya and Roque 2015) referring to ethical weaknesses of their research (Zavaleta et al 2007). They considered that the ethics requirements were fulfilled under the authorization of the Ministry of Health of Peru, the approval of the ethics committee of the Cayetano Heredia University, and the consent of the Chayahuita community leader.…”
mentioning
confidence: 99%
See 2 more Smart Citations